Addressing global challenges in geographical education: perspectives from the CGE Springer book series - Wilmot, Di; Brooks, Clare (International research in geographical and environmental education, 2024)
A key responsibility of academic scholarship is to further develop the field under investigation and to critically evaluate how it is responding to challenges from both inside and outside of the field of enquiry. This article offers an overview of whether the scholarship published in geography education (GE) from the perspective of the Commission for Geography Education (CGE) Springer book series is sufficiently engaging with contemporary global challenges and education discourses. Guided by the 2022 IGU-CGE Rennes Conference's three axes: curriculum renewal, pedagogy and teacher training, the article discusses the findings of a meta-analysis of the six books published in the CGE Springer series in the past five years (2017 to 2021).The thematic analysis shows that GE is engaging with global realities of environment and sustainability, climate change, globalisation and the importance of powerful knowledge for understanding and engaging with complex, often controversial issues. But there are also gaps and absences in terms of who is producing knowledge and from where knowledge is being generated. We contend that the book series is well placed to support the community in addressing global concerns and the related transformative pedagogies needed to enact them. However, we also suggest that the publications at this point in time have yet to fully grasp the specifics needed for the challenges that lie ahead. Some preliminary considerations for advancing the field through future publications are offered. These may be useful to GE researchers and scholars in different regions of the world.